A First Approach to the Experimental Study of Fracture Parametersin Opening and Mixed Mode by Caustics. (2015) - La Rosa, Guido; Savio, Fabio Lo
Abstract: Among the experimental methodologies used to determine the fracture parameters, considering the up-and-coming possibility of the caustics technique, the authors have started a search path to provide a setup and reliable test proceduresfor determining the K parameter inmode I and mixed mode. This work shows the set-up used and the first results. Firstly, the caustics for KI were obtained using a specific loading system to be used on an optical bench; then, the measurement system was transferred on a material testing machine in order to apply loads of greater magnitude. The results obtained are in agreement with the theoretical estimates in the opening mode and they may be considered promising for the analysis of mixed mode, although still substantially different from the values observed in the literature.